SYNTHESIS, CHARACTERIZATION AND THERMAL BEHAVIOUR OF HEAVY TRIVALENT LANTHANIDE MALONATES - José Roberto Locatelli; Cláudio Teodoro de Carvalho; Flávio Junior Caires; Massao Ionashiro (Eclética Química, 2018)
Solid-state Ln-L compounds, where Ln stands for heavy trivalent lanthanides (Tb-Lu) and L is malonate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, TG-FTIR system, elemental analysis and complexometry were used to characterize and to study the thermal behaviour of these compounds. The dehydration of the compounds begins at 303 K and the anhydrous compounds are stable up to 548 K. The results also provided information concerning the ligand’s denticity, thermal behaviour and identification of some gaseous products evolved during the thermal decomposition of these compounds.